Outline of an Anthropological Contribution to the Study of Snake Venom Variability: The Case of Echis sp. Envenomation - Tilman Musch (Ethnobiology Letters, 2014)
An understanding of the variability of snake venom composition is of high relevance for adequate treatment of snakebites. Clinical observations of bite victims are considered as a first step in the study of venom variability. The present paper suggests the study of local clinical observations made by healers as an anthropological contribution to the interdisci-plinary research of venom variability on a species and subspecies level. Such an anthropological contribution will take into account cultural particularities of a region. In order to illustrate his approach, the author describes his ethnozoological and ethnomedical fieldwork among Zarma and Tuareg in western Niger where he studied envenomation by Echis leucogaster. This species is of particular interest, as no medical descriptions of envenomation resulting from its bites seem to exist.